THE CONCEPT OF OWNERSHIP AND THE ROLE OF PROPERTY RIGHTS IN ECONOMIC SYSTEMS: https://doi.org/10.5281/zenodo.15828601 - Bozorboyev , Diyorbek (Journal of Contemporary World Studies, 2025)
The concept of ownership refers to the distribution of rights to control and use resources, production tools, or property within an economic system. It defines who owns resources and how they should be utilized. The theory of property rights emerged in the 1960s and 1970s and has since become a key methodological foundation for economic analysis, including law and economics, economic history, and organizational theory. Founders such as R. Coase and A. Alchian emphasized that ownership rights are not rigidly defined points but represent a continuous spectrum of powers distributed among different actors. According to the theory, ownership includes various elements such as possession, use, management, income collection, transfer, security, inheritance, and prohibition of harmful use.